Experimental Study of Oil Flow Visualization on the Analysis on Airfoil Eppler 562 of the Use of Forward and Rearward Wingtip Fences 75o Cant Angle Article - Dwi Cahyo, Bayu; Sakti, Gunawan; Wulansari, Ajeng; Junipitoyo, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In this study, the flow over airfoil Eppler 562 with and without wingtip was investigated experimentally. The experiments were carried out in a low speed wind tunnel with various angles of attack (α) = 0° to 19°. The Reynolds (Re) number used is 2.3 x 104 (U∞ = 10 m/s). There are two types of wingtip fences at variations that will be used in this research that are rearward and forward wing tip fence set at cant angle 75°. For this research, to represent flow patterns on airfoil the Oil flow visualization method was used. pressure transducer used to measure pressure distributions over the airfoil. The experimental results showed that as the angle of attack increased, the transition points and the separation moved towards the leading edge at all models. Furthermore, for airfoil withforward wingtip fence with cant angle 75° is better than for airfoil with rearward wingtip fence with cant angle 75° and plain wing. Forward wingtip fence showed the best optimum performance of α = 10° settings compared to the other models. Consequently, it was seen that there was a good agreement between numerical and experimental results.